Solidarity with the Dead: On Some Issues with the Depiction of Native (American) People in Hollywood - Pápai, Zsolt (AMERICANA E-journal of American Studies in Hungary, 2024)
From the 1950s onwards, Hollywood has broken with the racist portrayal of Natives found in classic Westerns of previous decades, yet the emancipation/rehabilitation of Natives has still barely succeeded. This is due to the evaluative principles and value perspectives of Hollywood films. Hollywood films are structurally unsuitable for the emancipation/rehabilitation of Natives. This paper proves this assertion in three steps. First, we will briefly review the situation before the supposed turning point of the 1950s and outline the paradigm shift of the fifties. In the second step, we examine the image of the hero in Hollywood films and how compatible (or incompatible) it is with the portrayal of Native people in films. Finally, we will analyze the portrayal of Natives in a contemporary film, Killers of the Flower Moon (director: Martin Scorsese), released in 2023. The film was undoubtedly made with good intentions, but it is not free from the problems of representation of Natives. In the paper, we discuss the indigenous people and their descendants in the current territory of the United States, but we consistently avoid using the term “Native American”, opting instead for the simplified noun “Native”. The politically correct term “Native American” actually reflects the perspective of the white mainstream, making it incorrect. It interprets the homeland of the Natives as America, even though it was the conquering whites who named the continent America.